2018
DOI: 10.1111/jcmm.13632
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment‐induced PIM kinases promote CXCR4‐triggered mTOR pathway required for chronic lymphocytic leukaemia cell migration

Abstract: Lymph node microenvironment provides chronic lymphocytic leukaemia (CLL) cells with signals promoting their survival and granting resistance to chemotherapeutics. CLL cells overexpress PIM kinases, which regulate apoptosis, cell cycle and migration. We demonstrate that BCR crosslinking, CD40 stimulation, and coculture with stromal cells increases PIMs expression in CLL cells, indicating microenvironment‐dependent PIMs regulation. PIM1 and PIM2 expression at diagnosis was higher in patients with advanced diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…In support of this idea, MAPKAPK2 −/− neutrophils generated less O 2 − , and both NADPH-oxidase activation and p47 phox phosphorylation were decreased [ 79 ]. PIM kinases have been reported to promote cell migration and invasion [ 80 ], and participation of PIM1 in p22 phox -dependent signaling also was reported [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea, MAPKAPK2 −/− neutrophils generated less O 2 − , and both NADPH-oxidase activation and p47 phox phosphorylation were decreased [ 79 ]. PIM kinases have been reported to promote cell migration and invasion [ 80 ], and participation of PIM1 in p22 phox -dependent signaling also was reported [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the interaction of leukemia cells with bone marrow stromal cells has impact on their biology and response to therapy and can modify the phenotype of stromal cells , it is of particular importance to verify the drugs efficiency in a bone marrow mimicking conditions. Most of the co‐culture studies concentrate on the stroma‐mediated effects on leukemia cells . However, it is also very important to monitor the vital state of stromal cells, as they are a source of protective and proleukemic signals.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, using a mouse MM model, it has been reported that treatment with BTZ reduces CXCR4 expression, which might favor MM cell egress from the BM milieu and promote extramedullary disease (129). In CLL, CXCR4 expression is regulated by BTK and its downstream target PIM, and both kinases phosphorylate CXCR4 at Ser 339 (130, 131). Using the Eμ-TCL1 murine model of CLL (132), as well as human CLL cells, Chen et al (130) showed that BTK inhibition by ibrutinib decreased CXCR4 membrane expression along with a rapid release of CLL cells from spleen and LNs to the circulation.…”
Section: Chemokines and Their Receptors In Hematologic Tumor Cell Tramentioning
confidence: 99%
“…Using the Eμ-TCL1 murine model of CLL (132), as well as human CLL cells, Chen et al (130) showed that BTK inhibition by ibrutinib decreased CXCR4 membrane expression along with a rapid release of CLL cells from spleen and LNs to the circulation. In addition, inhibition of PIM by the small molecule SEL24-B489 also blocked CLL cell migration by reducing CXCR4 surface expression and CXCR4-dependent mTOR activation (131). For acute leukemias, it has been reported that calcineurin signaling promotes the expression of cortactin in T-ALL cells, which in turn controls the levels of CXCR4 at the surface of these tumor cells (133, 134).…”
Section: Chemokines and Their Receptors In Hematologic Tumor Cell Tramentioning
confidence: 99%